2018
DOI: 10.1016/j.celrep.2018.02.032
|View full text |Cite
|
Sign up to set email alerts
|

α Cell Function and Gene Expression Are Compromised in Type 1 Diabetes

Abstract: Many patients with type 1 diabetes (T1D) have residual β cells producing small amounts of C-peptide long after disease onset but develop an inadequate glucagon response to hypoglycemia following T1D diagnosis. The features of these residual β cells and α cells in the islet endocrine compartment are largely unknown, due to the difficulty of comprehensive investigation. By studying the T1D pancreas and isolated islets, we show that remnant β cells appeared to maintain several aspects of regulated insulin secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
210
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(234 citation statements)
references
References 34 publications
20
210
3
1
Order By: Relevance
“…Surprisingly, this process of beta cell loss has not so far been explored in T1D. Similar to the finding of PDX1 reactivity in the nuclei in a proportion of the alpha cells reported herein, a recent publication on impaired alpha cell function in T1D showed that most alpha cells in donors with T1D do not express the alpha cell transcription factors MAFB and ARX, but low levels of NKX6.1 [28]. Cells of a similar phenotype produce trace amounts of insulin, too low for detection by ordinary analysis [29].…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Surprisingly, this process of beta cell loss has not so far been explored in T1D. Similar to the finding of PDX1 reactivity in the nuclei in a proportion of the alpha cells reported herein, a recent publication on impaired alpha cell function in T1D showed that most alpha cells in donors with T1D do not express the alpha cell transcription factors MAFB and ARX, but low levels of NKX6.1 [28]. Cells of a similar phenotype produce trace amounts of insulin, too low for detection by ordinary analysis [29].…”
supporting
confidence: 72%
“…Pancreatic biopsies were obtained from six patients with recent-onset T1D, included in the DiViD study. Mean age was 28 years (range [24][25][26][27][28][29][30][31][32][33][34][35]. Biopsies were taken laparoscopically from the pancreas tail 3-9 weeks after diagnosis.…”
Section: Biopsiesmentioning
confidence: 99%
“…Human islets were perifused within 24 hours of arrival at Vanderbilt, as previously described (32,71,76), with DMEM supplemented with the following glucose concentrations and test agents: 5.6 mM glucose, 16.7 mM glucose, 16.7 mM glucose plus 100 μm IBMX, 1.7 mM glucose plus 1 μm epinephrine (MilliporeSigma), and 5.6 mM glucose plus 20 mM KCl (MilliporeSigma). Human insulin and glucagon secretion and content was measured in fractions and extracts by radioimmunoassay from MilliporeSigma (catalog no.…”
Section: Fl11mentioning
confidence: 99%
“…81 Therefore, studies of α-cell physiology, regulation of glucagon secretion and most importantly molecular and functional interactions between αand β-cells have increasingly caught attention, in particular with respect to the development and management of diabetes mellitus. [82][83][84][85][86][87][88] Although fundamental aspects concerning the circadian control of transcription and functional regulation in the context of the intact pancreatic islet have been largely explored (as highlighted in the previous chapter), studies aiming to zoom into pancreatic islet cells in order to decipher circadian clock function in different islet cell types have only recently emerged. Our own recent study focuses on the molecular characterization of the αand β-cellular clocks, their interactions, impact on gene transcription and islet hormone secretion.…”
Section: Body Metabolism Is Orchestrated By Circadian Clocks In Rodmentioning
confidence: 99%